2023
DOI: 10.1021/jacs.2c12437
|View full text |Cite
|
Sign up to set email alerts
|

Coaxially Conductive Organic Wires Through Self-Assembly

Abstract: Here, we describe the synthesis of the hexameric macrocyclic aniline (MA­[6]), which spontaneously assembles into coaxially conductive organic wires in its oxidized and acidified emeraldine salt (ES) form. Electrical measurements reveal that ES-MA­[6] exhibits high electrical conductivity (7.5 × 10–2 S·cm–1) and that this conductivity is acid–base responsive. Single-crystal X-ray crystallography reveals that ES-MA­[6] assembles into well-defined trimeric units that then stack into nanotubes with regular channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…developed a hexameric macrocyclic aniline 8 and the acidified emeraldine salt ES‐8 (Figure 6). [20] The crystal devices of ES‐8 were fabricated on Si/SiO 2 wafers and exhibited higher conductivity value up to 7.5×10 −2 S/cm −1 (Figure 6B). Single‐crystal X‐ray diffraction of ES‐8 revealed that macrocycles could assemble into trimers in the solid state.…”
Section: Macrocycles In Optoelectronic Device Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…developed a hexameric macrocyclic aniline 8 and the acidified emeraldine salt ES‐8 (Figure 6). [20] The crystal devices of ES‐8 were fabricated on Si/SiO 2 wafers and exhibited higher conductivity value up to 7.5×10 −2 S/cm −1 (Figure 6B). Single‐crystal X‐ray diffraction of ES‐8 revealed that macrocycles could assemble into trimers in the solid state.…”
Section: Macrocycles In Optoelectronic Device Materialsmentioning
confidence: 99%
“…Photo inset visually demonstrates the color difference between acidified ES‐8 (right) and basified ES‐8 (left). Reproduced with permission [20] . Copyright 2023, American Chemical Society.…”
Section: Macrocycles In Optoelectronic Device Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…35 In these wires, the topological and trivial structural limits can be controlled by the acidity of the environment because neutral amines are basic and the radical cations are acidic. 16 For C2[m], we envision that the nitrogen-containing molecules, which have been recently synthesized 36 but not studied as single-molecule circuits, could show novel conductance−length properties.…”
mentioning
confidence: 99%